The Influence Of Digital And Traditional Marketing Strategy On Consumer Behavior And Its Impact On Consumer Purchase Decision In Honey Products (Journal of Innovation, Business and Entrepreneurship, 2020)
Business competition in the culinary field is always being high competition and affects the food and beverage industry from producers to consumers. One of the sectors in the food and beverage industry is the honey industry. Honey goods developed from the area of health supplements development into the field of economic development. (Yeow et al., 2013). Nevertheless, in the market, we can see the price of the honey product, especially Raw Honey, is varied based on the Quality, the brand, and the marketing strategy. With this condition, every Honey company has a different marketing strategy to increase the revenue of the business, especially in the digital era. So, they have to choose rather than use traditional or digital marketing strategy as the primary marketing strategy for their strategic plan. Therefore, Hivellion Company, as one of the honey businesses, also finds it challenging to determine the right marketing strategy for its products to compete with other competitors and to solve high competitiveness in honey products. In this research, the author wants to analyze the influence of digital and traditional marketing strategies on consumer behavior and its impact on consumer purchase decisions of the Honey products. To get more data, Quantitative methods are used to obtained primary data for analysis from potential customers by giving the questionnaire to 175 respondents who buy honey products. To support this method, the authors use secondary data such as literature and journal. This paper will be useful for marketers, business owners, and especially for another party involved in culinary SMEs to understand the impact of digital and traditional marketing strategy and understand the importance of digital and traditional marketing strategy in order to attract purchase decisions of customers so they can get more sales from the product sold. Hopefully, they can understand how to design the strategy of digital marketing to attract customer purchase decisions so that they can implement this strategy in their business.Keywords: Digital Marketing, Traditional marketing, Consumer Behavior, Consumer Purchase Decision